1998
DOI: 10.1029/97wr03497
|View full text |Cite
|
Sign up to set email alerts
|

A Soil Moisture–Rainfall Feedback Mechanism: 2. Numerical experiments

Abstract: Abstract. Here we develop a numerical model to investigate the hypothesis proposed by a companion paper [Eltahir, this issue], which describes a soil moisture-rainfall feedback mechanism. The model is designed to describe the seasonal evolution of the West African monsoon rainfall and is used to perform numerical experiments that elucidate the mechanisms of the response of rainfall to soil moisture anomalies. A significant rainfall anomaly is simulated by the model in response to a hypothetical soil moisture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 37 publications
5
49
0
Order By: Relevance
“…Eltahir (1998) proposed a hypothesis to describe the physical mechanisms of soil moisture-rainfall feedback. In addition, Zheng (1998) confirmed this hypothesis in West African monsoon rainfall using a two-dimensional model.…”
Section: Introductionsupporting
confidence: 69%
“…Eltahir (1998) proposed a hypothesis to describe the physical mechanisms of soil moisture-rainfall feedback. In addition, Zheng (1998) confirmed this hypothesis in West African monsoon rainfall using a two-dimensional model.…”
Section: Introductionsupporting
confidence: 69%
“…According to Eltahir (1998), the soil mois-ture conditions over any large region should be associated with relatively large moist static energy in the boundary layer, which favours the occurrence of more rainfall. This hypothesis was also confirmed for West African monsoons by Zheng and Eltahir (1998). In this vein, van der Ent and Savenije (2011) quantified the spatial and temporal scale of moisture recycling independent of the size and shape of the region and found that approximately 70 % of the precipitation in the centre of the South American continent is of terrestrial origin, as in many regions of Africa but specifically in the CRB, where strong moisture feedback occurs.…”
Section: Moisture Contribution From the Sources: Forward Analysismentioning
confidence: 60%
“…Over Europe, Schär et al [1999] identified positive soil moisture-precipitation feedbacks using regional climate model (RCM) simulations. In West Africa, Zheng and Eltahir [1998] showed a positive soil moisture-rainfall feedback when imposing a large-scale soil moisture anomaly in their numerical experiments. A decrease of local rainfall in the wetlands of South Florida due to land use change was shown by Pielke et al [1999] using RCM experiments.…”
Section: Introductionmentioning
confidence: 99%
“…One final comment on land use change climate studies is that most of the numerical experiments imposed exaggerated changes in order to obtain statistical significance of the results. For example, the soil moisture anomaly in West Africa by Zheng and Eltahir [1998] was imposed over an exceptionally large area. Different results were obtained in the same region when realistic land use change was imposed.…”
Section: Introductionmentioning
confidence: 99%